2022
DOI: 10.3389/fphar.2022.1026199
|View full text |Cite
|
Sign up to set email alerts
|

Selenium-enriched yeast modulates the metal bioaccumulation, oxidant status, and inflammation in copper-stressed broiler chickens

Abstract: Copper (Cu) could be seriously hazardous when present at excessive levels, despite its vital contribution to various cellular processes. Selenium-enriched yeast (SeY) was reported to improve the health and metabolic status in broiler chicken. Hence, our study was endeavored to illustrate the mitigating efficacy of SeY on Cu-induced hepatic and renal damage. Cobb chicks aged 1 day were allocated into four experimental groups and offered a basal diet, SeY (0.5 mg/kg), CuSO4 (300 mg/kg), or SeY plus CuSO4 in thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Similar outcomes were also reported by Sadek and colleagues in cadmium chloride [ 54 ] and vancomycin [ 30 ]-mediated renal stresses. The ability of selenium to quench hydrogen peroxide radicals refers to its position as a selenocysteine residue in the active site of selenoproteins, including GPx [ 65 , 66 ]. Previous studies had reported that green synthetized SeNPs with phytochemicals offered a distinguished antioxidant power than that of SeNPs alone [ 26 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar outcomes were also reported by Sadek and colleagues in cadmium chloride [ 54 ] and vancomycin [ 30 ]-mediated renal stresses. The ability of selenium to quench hydrogen peroxide radicals refers to its position as a selenocysteine residue in the active site of selenoproteins, including GPx [ 65 , 66 ]. Previous studies had reported that green synthetized SeNPs with phytochemicals offered a distinguished antioxidant power than that of SeNPs alone [ 26 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining intestinal health is essential for the health status of poultry. When the body is in an oxidative stress state, there is an increase in MDA and the accumulation of ROS and a decrease in SOD, CAT, and GSH-Px, which aggregates the damage to cells and tissues, causing a series of health problems [ 23 , 24 ]. Excessive oxidative stress often induces inflammation [ 25 ] and promotes cells to produce inflammatory cytokines, such as IL-1β, IL-6, and TNF-α, and activate inflammatory responses [ 26 ].…”
Section: Discussionmentioning
confidence: 99%